[6π] photocyclization to cis-hexahydrocarbazol-4-ones: substrate modification, mechanism, and scope - Modha, Sachin G.; Dreuw, Andreas (The journal of organic chemistry, 2019)
Upon irradiation at λ = 366 nm, tertiary N-alkoxycarbonyl-N-aryl-β-enaminones furnished exclusively the trans-hexahydrocarbazol-4-ones by a conrotatory [6π] photocyclization but epimerized on silica to cis-hexahydrocarbazol-4-ones (14 examples, 44-98% yield). The acceptor substitution on the nitrogen atom enhanced the stability of the cyclized products compared to N-alkyl-N-aryl-β-enaminones reported previously. The mechanism of the [6π] photocyclization was investigated by quenching experiments, deuterium-labeling experiments, and DFT calculations, suggesting a triplet pathway for the conrotatory ring closure followed by a suprafacial [1,4] hydrogen migration.
Im Text wird pi als griechischer Buchstabe dargestellt
Gesehen am 20.11.2019